The effect of cash turnover and receivable turnover on profitability - ., Rusdiyanto; Dina Fitrisia Septiarini, Dian Agustia, Soegeng Soetedjo, (Opción, 2020)
This study aims to examine the effect of Cash Turnover and Receivable Turnover on the Profitability of Bank Rakyat Indonesia Inc. from 2016 to 2018. The method used in this research is descriptive method with a quantitative approach. The results of this study explain that the Cash Turnover Ratio has a value of 0.037> 0.005 that the Cash Turnover ratio has no effect on the profitability ratio of Bank Rakyat Indonesia Inc. In conclusion, the greater the ratio of accounts receivable turnover can affect the level of Profitability at Bank Rakyat Indonesia Inc.